Increasing social disparities in obesity among 15000 pre-schoolers in a German district from 2009 to 2019 - Michel, Zora; Krayl, Nele; Götz, Katja; Wienke, Andreas; Mikolajczyk, Rafael; Führer, Amand-Gabriel (European journal of public health, 2023)
Background: Although childhood obesity prevalence has stagnated in many high-income regions after decades of increase, it continues to be a major public health problem with adverse effects. The objective was to examine obesity trends as a function of parental social status to identify obesity disparities among children. Methods: Data from school entry examinations from 2009 to 2019 of 14 952 pre-schoolers in one German district were used. Logistic regression models (obesity/overweight as dependent variable) and a linear regression [BMI z-score (BMIz) as dependent variable] were performed adjusted for social status and sex to investigate time trends in overweight and obesity. Results: Overall, we found an increase of obesity over time [odds ratio (ORs): 1.03 per year, 95% CI: 1.01–1.06]. Children with low social status had an OR of 1.08 per year (95% CI: 1.03–1.13), while the trend was less expressed in children with high social status (OR: 1.03 per year, 95% CI: 0.98–1.08). The mean BMIz decreased per year (regression coefficient −0.005 per year, 95% CI: −0.01 to 0.0) when considering all children. This decrease was more pronounced in children with high social status (regression coefficient: −0.011 per year, 95% CI: −0.019 to −0.004), compared with a slight increase of 0.014 (95% CI: −0.003 to 0.03) per year among children with low social status. Also, children with low parental social status were heavier and smaller than their peers with high social status. Conclusions: Although the mean BMIz decreased among pre-schoolers, obesity prevalence and status-related inequity in obesity prevalence increased from 2009 to 2019 in the region studied.